PENERAPAN DIGITAL MARKETING PADA CV. PRIMA JAYA 2 - Johny Budiman; Supriyadi Arifin (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2024)
CV. Prima Jaya 2 is a business founded by Mr. Eng Kiong which has been established since 2002 until now. CV. Prima Jaya 2 is a medium-sized business that operates in the field of building materials such as sand, cement, brick, wood, electrical equipment, and others. CV. Prima Jaya 2 is located at Ruko Griya Prima Block G1 12A&B, Batu Aji District, Batam City, Riau Islands. As a developing MSME, CV. Prima Jaya 2 continues to make developments to support the development of its business. The research method used was observation and conducting interviews with business owners. Based on the research results, one of the business elements that must be updated by CV. Prima Jaya 2 is the implementation of digital marketing and payment options via transfer between accounts. In this modern era, every activity always involves technology to make work easier because limited knowledge and low mastery of technology is a problem for which a solution must be found for strategies to strengthen MSMEs. By providing solutions for CV. Prima Jaya 2 regarding the implementation of digital marketing can make it easier for MSMEs to become widely known and increase turnover for MSMEs